Recent Population of Banggai Cardinalfish (Pterapogon kauderni) in Kendari Bay – Southeast Sulawesi - Subhan, Subhan; Prayitno, Slamet Budi; Sabdaningsih, Aninditia; Asriyana, Asriyana (Department of Aquaculture, 2025)
The Banggai Cardinalfish, Pterapogon kauderni, has been introduced and spread in Kendari Bay, Southeast Sulawesi. The purpose of this study is to estimate the current fish density and distribution of microhabitats in Kendari Bay. Observations of fish populations used the belt transect method at 5 observation stations, with 4 replications per station. Overall fish density ranged from 82±10 individuals/100 m2 to 1,509±583 individuals/100 m2. The fish choose to associated with micorohabitats such as Diadema sp., (69.1%), fire coral from the genus Millepora (16.4%), Sea anemone (10.7%) and seagrass (3.8%). P. kauderni was observed coexisting with other fish species in microhabitats such as around seagrass roots and corals, without showing significant aggressive behavior. Considering its ecological adaptations, P. kauderni is potentially suitable for aquaculture systems that combine multiple species. With the right domestication approach, this species has great potential for development in a sustainable ornamental aquaculture industry.